Long‐term health‐related quality of life in young childhood cancer survivors and their parents. Issue 12 (4th October 2021) - Fardell, Joanna E.; Wakefield, Claire E.; De Abreu Lourenco, Richard; Signorelli, Christina; McCarthy, Maria; McLoone, Jordana; Osborn, Michael; Gabriel, Melissa; Anazodo, Antoinette; Alvaro, Frank; Lockwood, Liane; Walwyn, Thomas; et al.
Abstract: Purpose: Few studies have investigated the health‐related quality of life (HRQoL) of young childhood cancer survivors and their parents. This study describes parent and child cancer survivor HRQoL compared to population norms and identifies factors influencing child and parent HRQoL. Methods: We recruited parents of survivors who were currently <16 years, and >5 years postdiagnosis. Parents reported on their child's HRQoL (Kidscreen‐10), and their own HRQoL (EQ‐5D‐5L). Parents rated their resilience and fear of cancer recurrence and listed their child's cancer‐related late effects. Results: One hundred eighty‐two parents of survivors (mean age = 12.4 years old and 9.7 years postdiagnosis) participated. Parent‐reported child HRQoL was significantly lower than population norms (48.4 vs. 50.7, p < .009). Parents most commonly reported that their child experienced sadness and loneliness (18.1%). Experiencing more late effects and receiving treatments other than surgery were associated with worse child HRQoL. Parents' average HRQoL was high (0.90) and no different to population norms. However 38.5% of parents reported HRQoL that was clinically meaningfully different from perfect health, and parents experienced more problems with anxiety/depression (43.4%) than population norms (24.7%, p < .0001). Worse child HRQoL, lower parent resilience, and higher fear of recurrence was associated with worse parent HRQoL. Conclusions: Parents report that young survivors experience small but significant ongoing reductions in HRQoL. While overall mean levels of HRQoL were no different to population norms, a subset of parents reported HRQoL that was clinically meaningfully different from perfect health. Managing young survivors' late effects and improving parents' resilience through survivorship may improve HRQoL in long‐term survivorship.